Isu Penyelarasan Flight Information Region di atas Wilayah Natuna - Asep Adang Supriyadi; Masita Dwi Mandini Manessa; Rudy Agus Gemilang Gultom (Institut Transportasi dan Logistik Trisakti, 2018)
Citizen sentiment is essential to evaluate the support toward government program. In 2015, Indonesian government proposed an acceleration program on re-alignment on Flight Information Region above Natuna area. Since then, primary of discussion is often be held as a formal or informal event. The data collected from 210 respondent, which consist of pilots, military staff, ATC staff, and academician. Furthermore, this study uses TF-IDW weighting technique to cluster the argument as positive, neutral, and negative sentiment. The result shows that most of Indonesia aviation community (75%) argue that FIR management should base on sovereignty and safety. Moreover, FIR issue under economic, national security and management shows significant positive respond (>90%) while FIR management under Singapore shows a negative response (100%). The result indicates that the aviation community supports the national program Natuna FIR re-alignment.